Experiential Avoidance and Bulimic Symptoms among Men in Residential Treatment for Substance Use Disorders: A Preliminary Examination. Issue 1 (1st January 2018) - Elmquist, JoAnna; Shorey, Ryan C.; Anderson, Scott; Stuart, Gregory L.
ABSTRACT: There has been a growing focus on identifying factors that underlie and maintain bulimic symptoms and substance use disorders (SUDs), as both are associated with high mortality and poor clinical outcomes. Experiential avoidance has been an area of interest within both the eating disorder and SUD fields, as it is a robust risk factor for both disorders. No known research has examined the relationship between experiential avoidance and bulimic symptoms in a SUD treatment-seeking sample. Moreover, the extant literature has focused exclusively on female samples. The purpose of this exploratory study was to examine the relationship between bulimic symptoms and experiential avoidance within an understudied population: men in treatment for a SUD. Three separate hierarchical regression analyses were conducted to examine the following relationships: (1) experiential avoidance and bulimic symptoms; (2) experiential avoidance and alcohol use and problems; and (3) experiential avoidance and drug use and problems. Results demonstrated that, controlling for alcohol and drug use and problems, experiential avoidance was significantly associated with bulimic symptoms. Experiential avoidance was also significantly associated with alcohol use and problems and drug use and problems. These findings are preliminary and future research is needed to further examine this relationship.